2014
DOI: 10.1155/2014/284237
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Ni DopedSnO2

Abstract: Nickel (Ni) doped SnO 2 powder samples were prepared using solid-state reaction with dopant concentrations in the range of 3 at.% to 15 at.%. The influence of Ni doping on structural, optical, and magnetic properties of the powder samples has been investigated. All the Ni doped powder samples exhibited tetragonal structure of SnO 2 . A decrease in optical band gap was observed with increase of Ni doping levels. The vibrating sample magnetometer measurements revealed that the Ni doped SnO 2 powder samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…It is clear from the above discussion that Ni ions has been incorporated into the SnO 2 lattice and affect the semiconducting properties of the material by increasing the band gap energy. A decrease in optical band gap with increasing Ni concentration has been explained by many groups . However, to the best of our knowledge, very few reports are available in the literature for increase in band gap on increasing Ni dopant level…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is clear from the above discussion that Ni ions has been incorporated into the SnO 2 lattice and affect the semiconducting properties of the material by increasing the band gap energy. A decrease in optical band gap with increasing Ni concentration has been explained by many groups . However, to the best of our knowledge, very few reports are available in the literature for increase in band gap on increasing Ni dopant level…”
Section: Resultsmentioning
confidence: 96%
“…The experimental efforts on transition‐metal‐doped SnO 2 were accelerated on finding high‐temperature ferromagnetism with giant magnetic moment in transparent Co‐doped SnO 2−δ . Several reports on various techniques are available in literature for the synthesis of Ni‐doped SnO 2 , such as sol–gel, polymeric precursor, pulsed laser deposition, spin coating, hydrothermal, co‐precipitation method, solid‐state reaction, flash evaporation technique, etc. Ni‐doped SnO 2 showed decrease in band gap with increasing Ni‐doping levels and exhibited room‐temperature ferromagnetism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been understood that, with the increased concentration of dopant species, energy levels or overlapping orbitals increases and width of the band starts to increase, which cause a decrease in the band gap energy. The effect of various dopants to decrease the optical band gap has been explained by many groups who have suggested the alloying effect in the host compound and the presence of some impurity phases as the main cause to affect [16]. Surface morphology of prepared samples was studied by SEM.…”
Section: Resultsmentioning
confidence: 99%
“…4. And reported that the observed room temperature ferromagnetism was due to oxygen vacancies [5][6][7][8].The hysteresis loop shows a high coercive field (H c ) of 683 G. The observed magnetic moment is almost equal to that of magnetic moment of Ni doped In 2 O 3 nanoparticles prepared by solid state synthesis route method observed by Peleckis et al [9].…”
Section: Figure 4magnetic Hysteresis Loops (M-h) Of Itoandmentioning
confidence: 87%